( x 2 − y 2 + 1 ) 2 + 4 x 2 y 2 − x 2 − y 2 = 0
If x and y are real numbers that satisfy the equation above, find the closed form of the sum of the maximum and the minimum value of P = x 2 + y 2 .
Submit your answer to 2 decimal places
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
While I agree that P 2 − 3 P + 1 ≤ 0 , you currently only have a necessary, but not yet sufficient, condition.
What you next need to do, is to show that a pair of x , y exist. Namely, we have to set x = 2 1 − P 2 + 3 P − 1 and y = P 2 − x 2 . IE the work that we have to do, is to show that P > x .
If we expand everything in the given equation, we get:
x 4 + 2 x 2 y 2 + 2 x 2 + y 4 − 2 y 2 + 1 − x 2 − y 2 = 0
x 4 + ( 2 y 2 + 1 ) x 2 + ( y 4 − 3 y 2 + 1 ) = 0 .
Using quadratic formula to solve for x 2 , as well as the fact that x 2 must be positive, we get:
0 ≤ x 2 = 2 − 2 y 2 − 1 ± ( 2 y 2 + 1 ) 2 − 4 ( y 4 − 3 y 2 + 1 ) = ± 4 y 2 − 4 3 − y 2 − 2 1 .
To this end, the right-hand side must be positive, so we only take the positive square root. Moving on, we have:
0 ≤ 4 y 2 − 4 3 − y 2 − 2 1
y 2 + 2 1 ≤ 4 y 2 − 4 3
y 4 + y 2 + 4 1 ≤ 4 y 2 − 4 3
y 4 − 3 y 2 + 1 ≤ 0 .
Once again using the quadratic formula for y 2 , and knowing that a quadratic in y 2 will be negative between the two roots, we get:
2 3 − 5 ≤ y 2 ≤ 2 3 + 5 .
From here, by substituting for x 2 , note that P = x 2 + y 2 = ( 4 y 2 − 4 3 − y 2 − 2 1 ) + y 2 = 4 y 2 − 4 3 − 2 1 .
Since this function P is strictly increasing with regard to y 2 , we can say that the minimum and maximum of P occur at the minimum and maximum values of y 2 . So:
m i n ( P ) = 6 − 2 5 − 4 3 − 2 1 = 2 2 1 − 8 5 − 2 1 = 2 4 − 5 − 2 1 m a x ( P ) = 6 + 2 5 − 4 3 − 2 1 = 2 2 1 + 8 5 − 2 1 = 2 4 + 5 − 2 1 .
And thus, m i n ( P ) + m a x ( P ) = 2 ( 4 + 5 ) + ( 4 − 5 ) − 1 = 3 .
Problem Loading...
Note Loading...
Set Loading...
To solve this problem, you have to make P appeared in the equation ( x 2 − y 2 + 1 ) 2 + 4 x 2 y 2 − x 2 − y 2 = 0 ⇔ x 4 − 2 x 2 ( y 2 − 1 ) + ( y 2 − 1 ) 2 + 4 x 2 y 2 − x 2 − y 2 = 0 ⇔ x 4 + y 4 − 2 x 2 y 2 + 4 x 2 y 2 + 2 x 2 − 2 y 2 − x 2 − y 2 + 1 = 0 ⇔ ( x 2 + y 2 ) 2 − 3 ( x 2 + y 2 ) + 1 = − 4 x 2 ≤ 0 ; ∀ x ∈ R ⇒ P 2 − 3 P + 1 ≤ 0 ⇔ 2 3 − 5 ≤ P ≤ 2 3 + 5 So the sum is 3 . 0 0